2018
DOI: 10.1161/jaha.118.010134
|View full text |Cite|
|
Sign up to set email alerts
|

“It's Like They Forget That the Word ‘Health’ Is in ‘Home Health Aide’”: Understanding the Perspectives of Home Care Workers Who Care for Adults With Heart Failure

Abstract: Background Home care workers ( HCW s) increasingly provide long‐term and posthospitalization care for community‐dwelling adults with heart failure ( HF ). They observe, assist, and advise these patients, yet few studies have examined their role in HF . As the foundation for future interventions, we sought to understand the perspectives of HCW s caring for adults with HF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…5 Home care workers are essential to the health of more than 7 million older adults who require care in the home. 6,7 In this issue of JAMA Internal Medicine, Sterling and colleagues 8 present the findings from in-depth interviews with 33 unionized home care workers (64% Black/African American participants, 18% Latinx/Hispanic participants, and 97% women) across the 5 boroughs of New York City. Thanks to the quick leveraging of relationships between a medical school and a union chapter, the highly efficient use of a skilled qualitative research team, and meticulous inductive qualitative analysis, the authors have provided a window into the vulnerability of home care workers during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Home care workers are essential to the health of more than 7 million older adults who require care in the home. 6,7 In this issue of JAMA Internal Medicine, Sterling and colleagues 8 present the findings from in-depth interviews with 33 unionized home care workers (64% Black/African American participants, 18% Latinx/Hispanic participants, and 97% women) across the 5 boroughs of New York City. Thanks to the quick leveraging of relationships between a medical school and a union chapter, the highly efficient use of a skilled qualitative research team, and meticulous inductive qualitative analysis, the authors have provided a window into the vulnerability of home care workers during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being integral to patient care, home health care workers-who are mostly middle-age women, people of color, and immigrants-are often an invisible and vulnerable workforce. 5,7 They work long hours, earn minimum wages, and have limited opportunities for career advancement. 8,9 Indeed, 1 of every 6 workers lives below the federal poverty line.…”
mentioning
confidence: 99%
“…24 In light of this, previous research has highlighted the limited training that home care workers receive on heart failure symptoms and management. 12,[14][15][16] Given that heart failure has unique needs and disease trajectory and that home care workers' scope of care differs from that of family caregivers and healthcare providers, this study identified their educational needs and priorities as paid caregivers caring for heart failure patients at the end-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…13 A majority of home care workers do not receive systematic training on and feel ill-equipped to provide endof-life care for heart failure patients. 12,[14][15][16] States in the U.S. have invested funds towards the training and development of home health workers; however, limited research has explored their training needs. 17 To address this gap, we elicited the educational needs and priorities of home care workers caring for community-dwelling adults with heart failure at the end-of-life.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their role providing direct care to people with complex or fragile health conditions, home care workers are often an invisible sector of the healthcare workforce. [9][10][11][12] For these workers, social distancing is seldom possible. Although personal protective equipment (PPE) can help protect against transmission, [13][14][15] research shows that other than disposable gloves, the home care sector has lower access to PPE than other healthcare settings.…”
mentioning
confidence: 99%